Targeting replication stress in cancer therapy - da Costa, Alexandre André B A; Chowdhury, Dipanjan; Shapiro, Geoffrey I; D'Andrea, Alan D; Konstantinopoulos, Panagiotis A (Nature reviews. Drug discovery, 2023)
Replication stress is a major cause of genomic instability and a crucial vulnerability of cancer cells. This vulnerability can be therapeutically targeted by inhibiting kinases that coordinate the DNA damage response with cell cycle control, including ATR, CHK1, WEE1 and MYT1 checkpoint kinases. In addition, inhibiting the DNA damage response releases DNA fragments into the cytoplasm, eliciting an innate immune response. Therefore, several ATR, CHK1, WEE1 and MYT1 inhibitors are undergoing clinical evaluation as monotherapies or in combination with chemotherapy, poly[ADP-ribose]polymerase (PARP) inhibitors, or immune checkpoint inhibitors to capitalize on high replication stress, overcome therapeutic resistance and promote effective antitumour immunity. Here, we review current and emerging approaches for targeting replication stress in cancer, from preclinical and biomarker development to clinical trial evaluation.